Spontaneous uterine rupture in early pregnancy: a systematic review of case reports and clinical outcomes - Singh, Adarsh K.; Yadav, Pooja; Asif, Shafaque; Shukla, Manu; Samaiya, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Spontaneous uterine rupture in early pregnancy is rare but life-threatening complication. First-trimester ruptures often present atypically and are under-represented in literature. This review aims to analyze reported cases of uterine rupture occurring before 16 weeks of gestation to identify clinical features, diagnostic challenges, management strategies and maternal outcomes. A comprehensive search was conducted using PubMed, Scopus, Embase, Cochrane Library and Google Scholar databases including articles published up to March 2025. Data on patient demographics, prior uterine surgeries, presenting complaints, imaging findings, surgical intervention, histopathology and clinical outcomes were extracted. Original case reports or case series in English language reporting spontaneous uterine rupture occurring before or at 16 weeks with adequate details were included in the study. Data was extracted independently by two reviewers using a standardized Excel spreadsheet. Descriptive statistics including means, frequencies and percentages were calculated. Eleven studies comprising 12 patients were included. Mean age was 31 years, with most patients being multiparous. Prior caesarean section or uterine surgery was identified in four patients and eight cases had unscarred uteri. Fundal rupture was most common site. Hemoperitoneum on ultrasonography and acute abdominal pain were common presenting features. Eight patients underwent uterine repair and four required hysterectomy. No maternal deaths were reported. This review emphasizes need for high clinical suspicion and prompt surgical intervention in early pregnancy rupture, even in absence of traditional risk factors.